2017
DOI: 10.18632/oncotarget.19712
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity for IFN-gamma production as a supportive diagnostic marker for gastric cancer

Abstract: Background/AimDecreased Natural killer cell activity (NKA) for interferon-gamma production (NKA-IFNγ) has been reported in cancer patients. The aim of this study was to determine the diagnostic performance of NKA-IFNγ for gastric cancer (GC).ResultsNKA-IFNγ levels were decreased in 261 GC patients with all stages of tumor compared to those in 48 healthy donors (P < 0.001), and lower levels of NKA-IFNγ were associated with higher GC stages. NKA-IFNγ levels were also associated with clinicopathological parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 33 publications
5
55
0
1
Order By: Relevance
“…Several studies have reported that the sensitivity and specificity of the NK cell activity test for colorectal cancer (cut-off value 181 pg/mL) were 87% and 61%, respectively; those for gastric cancer (cut-off value 438 pg/mL) were 67% and 92%, respectively; and those for prostate cancer (cut-off value 531 pg/mL) were 72% and 74%, respectively. 3 4 19 However, data on the relationship between physical activity and metabolic status with NK cell activity are limited. Using this simple test, we were able to conduct a large-scale study to determine if NK cell activity differs according to physical activity and metabolic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that the sensitivity and specificity of the NK cell activity test for colorectal cancer (cut-off value 181 pg/mL) were 87% and 61%, respectively; those for gastric cancer (cut-off value 438 pg/mL) were 67% and 92%, respectively; and those for prostate cancer (cut-off value 531 pg/mL) were 72% and 74%, respectively. 3 4 19 However, data on the relationship between physical activity and metabolic status with NK cell activity are limited. Using this simple test, we were able to conduct a large-scale study to determine if NK cell activity differs according to physical activity and metabolic status.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Several studies have reported that low NK cell activity is associated with an increased cancer risk, suggesting a role in natural host defense mechanisms against cancer. 2 3 4 5…”
Section: Introductionmentioning
confidence: 99%
“…Natural killer (NK) cells are large granular lymphocytes that play an important role in innate immunity, and are involved in the early defense against cancers and infections [1]. Several studies have reported that low NK cell activity is associated with an increased cancer risk, suggesting its role in the natural immunological host defense mechanisms against cancer [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, several recent studies showed that the decline in NK cell activity is related to various types of cancer. As a result, NK cells are now known to play a role in cancer cell immunological surveillance.…”
Section: Introductionmentioning
confidence: 99%